A distributed hierarchical control framework in islanded microgrids and its agent-based design for cyber-physical implementations - Nguyen, Tung-Lam (2022)
In this article, a distributed hierarchical control framework with coordinated secondary and tertiary levels is proposed for islanded microgrids (MGs). The structure and functionality of each agent are formulated to process simultaneously the secondary control and TC in a peer-to-peer communication network. First, the distributed secondary control is proposed for restoring system frequency/voltage while providing power sharing considering droop coefficients and upper level power dispatch orders. Then the distributed TC minimizes the network power loss in the islanded MG by using alternating direction method of multipliers (ADMM) algorithm. The multiagent system is designed to cover both control levels for cyber-physical implementations. A laboratory cyber-physical MG platform has been built to validate the proposed control framework in real-time and hardware-in-the-loop conditions. A six-bus three-DG MG is implemented on the platform and the experimental results validate the effectiveness of the proposed method.